Advanced lesions of synchronous bilateral mammary Paget’s disease: a case report - Lina Choridah; Wida Kartika Sari; Ery Kus Dwianingsih; Irianiwati Widodo; Suwardjo; Sumadi Lukman Anwar (Journal of Medical Case Reports, 2020)
Abstract Background Mammary Paget’s disease is an eczematous eruption on the nipple and areola with underlying breast malignancy. It is often misinterpreted as chronic dermatitis or psoriasis causing a delayed diagnosis. Synchronous bilateral mammary Paget’s disease is exceptionally rare and an advanced case with underlying invasive carcinoma might require long-term treatment and follow-up that could affect a patient’s physical, psychological, and social aspects of well-being. Case presentation A 54-year-old Javanese woman presented in our clinic with a 2-year history of itching and chronic eczema in both areolae. Bilateral nipple retraction and retro-areolar palpable lumps were observed during the first presentation. Breast ultrasound revealed hypoechoic lesions in her left and right breasts. Mammograms showed an irregular hyperdense lesion and multiple microcalcifications. Histopathology from biopsy and bilateral mastectomy demonstrated infiltration of large Paget’s cells in the epidermis of the areola with underlying lesions of invasive ductal carcinoma, diagnosed solid type with high nuclear grade and negative expression of estrogen receptor and progesterone receptor, with positive expression of human epidermal growth receptor-2(HER2) and Ki-67 (45%). Conclusions In a patient with suspicious chronic inflammation of the nipple and areolae, prompt biopsy should be performed to avoid a delayed diagnosis of any malignant breast lesion.